Development of Game-Based Karate Basic Technique Activities at Dojo Parulian 2 Medan - Mahmuddin; Riza, Ade Ros; Ishak, Muhammad; Silwan, Argubi (Journal Coaching Education Sports, 2025)
This study aims to develop game-based karate movement activities that can increase the effectiveness of training and active participation of Dojo Parulian 2 Medan members categorized as elementary schools aged 6 to 12 years. This research uses the Research and Development (R&D) research method developed by Sugiyono. With eight stages, namely potential and problems, collecting data, product design, design validation, design revision, product trial, product revision, trial use. This research was conducted at dojo Parulian 2 Medan with a small scale trial of 10 people and a large scale trial of 15 people. Based on the results of data analysis, it shows that the product quality assessment "Development of game-based karate movement activities in dojo parulian 2 medan" from the initial stage to the final stage is included in the "very feasible" criteria. The results of the analysis of the use trial to students stated "Very Feasible" with the results of a small scale trial with a score of 83.33% and a large scale trial with a score of 88.54%. From the results of the usage trial assessment, it can be concluded that the development of game-based karate motion activities at the Parulian 2 Medan dojo is categorized as "Very Feasible" and researchers can produce products for the implementation of game-based karate motion activity development.